Carbon‐ion radiotherapy versus radiofrequency ablation as initial treatment for early‐stage hepatocellular carcinoma. Issue 12 (3rd September 2022) - Fujita, Naoto; Kanogawa, Naoya; Makishima, Hirokazu; Ogasawara, Sadahisa; Maruta, Susumu; Iino, Yotaro; Shiko, Yuki; Kanzaki, Hiroaki; Koroki, Keisuke; Kobayashi, Kazufumi; Kiyono, Soichiro; Nakamura, Masato; et al.
Abstract: Aim: Carbon‐ion radiotherapy (C‐ion RT) has shown potential as a curative treatment for patients with hepatocellular carcinoma (HCC). However, no reports have compared the effectiveness of C‐ion RT and radiofrequency ablation (RFA). This study aimed to compare clinical outcomes between C‐ion RT and RFA for patients with early‐stage HCC. Methods: Medical records of consecutive patients with HCC (single lesion ≤5 cm or two to three lesions ≤3 cm) who received either C‐ion RT or RFA as initial treatment were retrospectively reviewed. Propensity score matching (PSM) was used to adjust for clinical factors between both groups. Results: A total of 560 patients were included, among whom 69 and 491 received C‐ion RT and RFA, respectively. After PSM (C‐ion RT, 54 patients; RFA, 95 patients), both groups were well balanced. Carbon‐ion radiotherapy had significantly lower cumulative intrasubsegmental recurrence rate after PSM compared to RFA ( p  = 0.004) (2‐year, 12.6% vs. 31.7%; 5‐year, 15.5% vs. 49.6%, respectively). However, no significant difference in cumulative local recurrence rate, stage progression‐free survival, or overall survival (OS) was observed between both groups. In the RFA group, 6 of 491 patients (1.2%) showed grade 3 adverse events, whereas no grade 3 or higher adverse events were observed in the C‐ion RT group. Conclusion: Carbon‐ion radiotherapy provided a lower cumulative intrasubsegmental recurrence rate, but a comparable cumulative local recurrence rate, stage progression‐free survival, and OS compared to RFA. Thus, C‐ion RT appears to be one of the effective treatment options for early‐stage HCC when RFA is deemed not indicated.